The influence of the PATHS curriculum on children's social-emotional competence - Dwi Ajni Shafarwati (Curricula: Journal of Curriculum Development, 2023)
Preschool-aged children tend to have a wide range of social-emotional skills and problems, making it difficult for them to enter school, leading to negative peer relationships and low academic achievement. Programs must support children in learning important skills early to perform socially appropriate actions, such as social behavior and coping skills. Prevention focuses on reducing aggressive and disruptive behaviors in children and developing children's social-emotional competencies. One of the preventions is the PATHS (Promoting Alternative Thinking Strategies) program. Based on this, the researcher tried to examine the effect of the PATHS curriculum on social-emotional competence in preschool and elementary school children. The method used in this article is a Systematic Literature Review. There are three stages in the Systematic Literature Review: searching and filtering the literature, analyzing the literature, and writing the analysis results in scientific arguments. The results show that PATHS will provide long-term effects if applied as prevention rather than treatment in preschool and elementary school-aged children. Because at that age, children are not yet able to control their emotions, which impacts social competence when attending school.